Detection of modified forms of cytosine using sensitive immunohistochemistry - Abakir, Abdulkadir; Wheldon, Lee M.; Johnson, Andrew D.; Laurent, Patrick; Ruzov, Alexey (Journal of Visualized Experiments, 2016)
Methylation of cytosine bases (5-methylcytosine, 5mC) occurring in vertebrate genomes is usually associated with transcriptional silencing. 5-hydroxylmethylcytosine (5hmC), 5-formylcytosine (5fC), and 5-carboxylcytosine (5caC) are the recently discovered modified cytosine bases produced by enzymatic oxidation of 5mC, whose biological functions remain relatively obscure. A number of approaches ranging from biochemical to antibody based techniques have been employed to study the genomic distribution and global content of these modifications in various biological systems. Although some of these approaches can be useful for quantitative assessment of these modified forms of 5mC, most of these methods do not provide any spatial information regarding the distribution of these DNA modifications in different cell types, required for correct understanding of their functional roles. Here we present a highly sensitive method for immunochemical detection of the modified forms of cytosine. This method permits co-detection of these epigenetic marks with protein lineage markers and can be employed to study their nuclear localization, thus, contributing to deciphering their potential biological roles in different experimental contexts.